Conclusion: the central role of human and social capital. Issue 2 (15th March 2017) - Redding, Gordon; Rowley, Chris
Abstract: The roles of human and social capital in fostering societal stability and progress are analyzed here in the basis of a series of empirical studies in the Asian region, each illuminating a separate aspect of the overall question: how does culture play a part in the socio-political economy? The studies cover the response of people in the Indonesian tourism industry to radical market changes; the impact of western-inspired management tools on workers in the Thai and Vietnamese industrial complexes; the ways in which credentials play a part in regional professional networking; the impact of worsening environment threats from flooding on workforce location and organizing; the not-always-benign workings of regional business networks of personal reciprocity; and the managerial ideology of many Indonesian companies. Human and social capital are illustrated here as largely invisible but still significant catalysts in the complex dynamics of countries striving to establish their own formulae for prosperity.